Exploring the impact of chronic urticaria profile as a key predictor of alexithymia: A cross‐sectional study - Ivan Cherrez‐Ojeda; Simon Francis Thomsen; Ana M. Gimenez‐Arnau; Jennifer Astrup Sørensen; Hermenio Lima; Kiran Godse; Carole Guillet; Luis Escalante; Astrid Maldonado; Gonzalo Federico Chorzepa; Blanca Morfin‐Maciel; Jose Ignacio Larco Sousa; et al. (Clinical and Translational Allergy)
Abstract Introduction The relationship between chronic urticaria (CU) and alexithymia, a cognitive‐affective impairment characterized by difficulty in identifying and expressing emotions, is complex and underexplored. This study aimed to identify predictors of alexithymia in CU patients by focusing on the impact of coexisting mental illnesses and antihistamine use. Methods An online survey was distributed to specialized allergy and dermatology centers from 2021 to 2022. The survey included the TAS‐20, UAS‐7, UCT, CU‐Q2oL, and demographic information. Participants were 18–80 years old, diagnosed with CU, and had no prior diagnosis of alexithymia. The final analysis included a total of 332 respondents from various countries. Regression models were used to investigate the relationship between clinical and demographic factors of patients with CU as key predictors of alexithymia. Results Among CU patients, the main predictors of having alexithymia were: presenting mental (OR = 2.406, p < 0.05) and cardiovascular comorbidities (OR = 2.085, p < 0.05), active urticaria (as opposed to being urticaria‐free), OR = 1.989, p < 0.05, severe impact on quality of life (OR = 1.973, p < 0.01), and the use of oral first‐generation antihistamines (OR = 2.340, p < 0.05). The duration of chronic urticaria diagnosis and other types of treatments (sg‐AH use, omalizumab use, and corticosteroid use) do not appear to be significantly associated with alexithymia. Conclusions Alexithymia is closely linked to clinical and demographic variables among patients with CU. These findings suggest that comprehensive management of CU should include psychological assessment and support, especially for patients with alexithymia and those using fg‐AH. Reducing the reliance on fg‐AH and addressing mental health issues may improve outcomes for these patients.